2005
DOI: 10.1177/1049732304272965
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Adherence in a Diabetes Patient: Transformations in Psychotherapy

Abstract: The authors present a case study of a 26-year-old woman who developed diabetes in early adolescence and who attended seven CAT sessions. They used phenomenology to analyze therapy transcripts, case notes, and a reflexive journal and extract the major themes. The client's identity had been overshadowed by the development of a "diabetic identity" that the client rejected. Poor adherence was linked to the rejection. Motivation to manage her diabetes changed during the CAT sessions once her identity was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 16 publications
5
67
0
Order By: Relevance
“…The identity change of the participant is significant because her transformative progress confirms previous research (Tilden et al, 2005), and this study also showed that an individual could shift from being "a victim of circumstances to a creator of circumstances" (Barroso, 1995 p. 44;Paterson et al, 1999, p 788).…”
Section: Integration Of the Nurse Identity Into Self-identitysupporting
confidence: 70%
See 4 more Smart Citations
“…The identity change of the participant is significant because her transformative progress confirms previous research (Tilden et al, 2005), and this study also showed that an individual could shift from being "a victim of circumstances to a creator of circumstances" (Barroso, 1995 p. 44;Paterson et al, 1999, p 788).…”
Section: Integration Of the Nurse Identity Into Self-identitysupporting
confidence: 70%
“…The progress of the participant in the present study parallels the research findings of Tilden et al (2005). Self-integrity developed as frequent challenges arose that required the participant to face critical situations.…”
Section: Integration Of the Nurse Identity Into Self-identitysupporting
confidence: 53%
See 3 more Smart Citations